Guardianship of real property in cases of double registration - Sánchez Coronado, Carlos Alberto (2023)
When an immovable property has been registered twice in the name of different people, they end up taking the case to a civil judge who requests that the property right that each one alleges corresponds to them be protected by the best property right or claim.This article criticizes the fact that these cases are resolved with registration principles, such as preference, opposability, and public faith in registration, which collapse by pulverizing the registration itself at the beginning of the real folio. In these circumstances, first of all, it must be verified if any of the contenders has consummated the acquisitive prescription. In the absence of this, it is necessary to certify the titles from which the disputed rights derive to apply the prior tempore potior iure principle in order to protect the contender who has the oldest title or who is included in the oldest chain of owners, therefore, opposable for having been the first to acquire the right, but not for having been the first to register their title.